2005
DOI: 10.1111/j.1540-8183.2005.04065.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Safety of Warfarin in Combination with Antiplatelet Therapy for Patients Treated with Coronary Stents for Acute Myocardial Infarction

Abstract: The safety and efficacy of treating recently stented patients on combination antiplatelet therapy with warfarin for clinical indications in unknown. Therefore, we examined the use of warfarin in a population of patients with myocardial infarction (MI) treated with coronary stenting. We performed a retrospective analysis comparing patients who underwent successful coronary stenting for acute MI and were discharged on either warfarin and combination platelet therapy for clinical indications or combination antipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 10 publications
3
48
0
3
Order By: Relevance
“…AF, prosthetic heart valves, venous thromboembolism and LVMT) already on DT can be a problem, as the risk of bleeding from prolonged therapy with aspirin, clopidogrel and warfarin is poorly understood. Two retrospective studies [46, 47] have attempted to analyze the safety and efficacy of triple therapy and found higher rates of bleeding or need for transfusion. Another large population-based observational cohort study [48] from Canada studied 21,443 elderly survivors of acute MI over a 4-year period for any hospitalization for bleeding and found a trend toward increased bleeding with triple therapy.…”
Section: Optimal Antithrombotic Regimens In Special Circumstancesmentioning
confidence: 99%
“…AF, prosthetic heart valves, venous thromboembolism and LVMT) already on DT can be a problem, as the risk of bleeding from prolonged therapy with aspirin, clopidogrel and warfarin is poorly understood. Two retrospective studies [46, 47] have attempted to analyze the safety and efficacy of triple therapy and found higher rates of bleeding or need for transfusion. Another large population-based observational cohort study [48] from Canada studied 21,443 elderly survivors of acute MI over a 4-year period for any hospitalization for bleeding and found a trend toward increased bleeding with triple therapy.…”
Section: Optimal Antithrombotic Regimens In Special Circumstancesmentioning
confidence: 99%
“…From 625 initial citations, 16 eligible studies including a total of 9185 patients were identified in the present meta‐analysis,4, 5, 6, 7, 12, 14, 15, 19, 20, 21, 22, 23, 24, 25, 26, 27 with 5680 patients in the triple therapy group and 3505 in the dual therapy group (Figure 1). …”
Section: Resultsmentioning
confidence: 99%
“…Finally, 12 studies were identified in the DAPT subgroup,4, 5, 6, 7, 19, 20, 21, 22, 23, 24, 25, 26 with the other 4 studies included in the OAC/C subgroup 12, 14, 15, 27…”
Section: Resultsmentioning
confidence: 99%
“…Observational data demonstrate a higher rate of bleeding with triple therapy than with antiplatelet therapy alone. 38 Warfarin is still the most effective agent in many settings, so its use in combination with other antithrombotics is often unavoidable. 39 …”
Section: Anticoagulants and Platelet Inhibitorsmentioning
confidence: 99%